Adenosine Formed by CD73 on T Cells Inhibits Cardiac Inflammation and Fibrosis and Preserves Contractile Function in Transverse Aortic Constriction–Induced Heart Failure. (April 2017) - Quast, Christine; Alter, Christina; Ding, Zhaoping; Borg, Nadine; Schrader, Jürgen
Abstract : Background—: Structural damage during heart failure development leads to increased infiltration of leukocytes. Because purinergic signaling on immune cells may impact on the inflammatory response, we evaluated the role of ecto-5′-nucleotidase (CD73) on the development of heart failure after transverse aortic constriction (TAC) using global and T-cell–specific CD73 − /− mice. Methods and Results—: Leukocytes infiltrating the failing heart were analyzed by a multistep enzymatic procedure over a period of 16 weeks using fluorescence-activated cell sorting. TAC significantly enhanced the infiltration of leukocytes, especially T cells. The fraction of CD73 expressing cells increased over time exclusively on cytotoxic T cells, T-helper cells, and regulatory T cells. Cardiac function significantly declined in T-cell–specific CD4-Cre +/ − CD73 flox/flox mice identical to that observed in global CD73 mutants and was associated with enhanced fibrosis (collagen, laminin, vimentin, periostin). Expression analysis by quantitative reverse transcription polymerase chain reaction of extracellular purine degrading enzymes and P1 and P2 receptors on T cells isolated from the injured heart revealed profound upregulation of the enzymatic machinery for hydrolysis of extracellular adenosine triphosphate and nicotinamide adenine dinucleotide, both pathways converging in the formation of AMP and adenosine via CD73. Among the P1 receptors, only the A2a receptor was significantly upregulated after TAC. T cells isolated from TAC-treated hearts show enhanced production of proinflammatory cytokines (interleukin-3, interleukin-6, interleukin-13, interleukin-17, macrophage inflammatory proteins-1α, and macrophage inflammatory proteins-1β) when CD73 was lacking. Conclusions—: Our data provide first evidence that CD73 on T cells plays an important anti-inflammatory role in TAC-induced heart failure, which is associated with antifibrotic activity and reduced production of proinflammatory cytokines most likely by activation of the adenosine A2a receptor. Abstract : Supplemental Digital Content is available in the text.